EVALUATING EFFECTIVENESS OF LASER PHOTOCOAGULATION AND INTRAVITREAL ANTI-VEGF INJECTIONS IN STAGE III RETINOPATHY OF PREMATURITY - Juneja, Stuti Vikas; Patel, Diti; Rathod, Afsa (International Journal of Retina, 2024)
Purpose: To compare the effectiveness of anti VEGF and laser photocoagulation treatment in stage III retinopathy of prematurity in infants at tertiary care hospital in central Gujarat. Methods: This was a comparative prospective and retrospective observational study. 60 infants were diagnosed with stage III retinopathy of prematurity from which 20 infants were treated with laser and 40 infants treated with anti VEGF injection of 0.25 mg/0.025 mL Ranibizumab. Efficacy of both the treatments were compared in terms of regression of disease clinically. All Demographic and medical data was analyzed using MS excel for finding frequency, percentages and associations applying Chi-squared test and by Epi info™ (version-7.2.5). Result: In this study 32(80%) infants who received anti VEGF and 8(40%) infants who received laser treatment showed stopped progression of neovascularization in single dose. Only 8(20%) infants needed re-treatment anti VEGF injection while 11(55%) infants required re-treatment laser therapy. So there was a statistically significant higher recurrence rate among infants who underwent laser therapy as compared to infants who underwent anti VEGF therapy (P=0.006).1(5%) infant lost both his eyes even after being treated with 2 sittings of laser treatment and who was <800g and very pre term birth so even with effort to treat, there was no regression and infant developed retinal detachment in both eyes. Conclusion: Both the treatments are effective for treating ROP stage III infants but higher recurrence rate was found among infants who underwent laser therapy as compared to anti VEGF therapy.